2010
DOI: 10.1007/s10509-010-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

The rotation signal in daily sunspot areas

Abstract: The continuous complex Morlet wavelet transform is used to investigate temporal rotation cycle length of daily sunspot areas from May 9, 1874 to February 28, 2010, from a global point of view. The rotation cycle length of the Sun is found to have a secular trend: it decreased from the year of 1874 to 1950s, and since then the Sun is rotating more and more speedily in the long run. The rotation period appears around the maximum times of the Schwabe cycles with statistical significance, but in the minimum times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…A weak decreasing trend is found in the coronal rotation cycle length, but this is statistically insignificant. However, for sunspots, a secular decreasing trend has been found in the Sun’s rotation cycle length, which is statistically significant (Li et al 2011a,b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A weak decreasing trend is found in the coronal rotation cycle length, but this is statistically insignificant. However, for sunspots, a secular decreasing trend has been found in the Sun’s rotation cycle length, which is statistically significant (Li et al 2011a,b).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, no secular trend is found to be statistically prominent. Li et al (2011a,b) have also found a secular decreasing trend in the length of the Sun’s rotation cycle by analysing sunspot activity. Furthermore, such a trend is statistically significant.…”
Section: Long‐term Variations Of the Coronal Rotation And Solar Actmentioning
confidence: 97%
“…Previous studies (see Heristchi & Mouradian 2009;Li et al 2011a;Xie et al 2012Xie et al , 2017b on the secular trend of the solar rotation period have often revealed a general decreasing trend in the solar rotation period. It should be pointed out that these studies focused on the sunspot activity and the corona radio flux.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…That is to say, in the local wavelet power spectra shown in Figure 7, the rotation period length at a certain time point has the highest power spectrum among the periodic scales of 24-30 days, where are the length range of coronal rotation period located . Based on this conception, the rotation period length of sunspot numbers (Li et al 2011a;Xie et al 2012), sunspot areas (Li et al 2011b), solar mean magnetic field (Xie et al 2017a), and 10.7 cm solar radio flux (Xie et al 2017b) are studied and estimated. In this sense, the similar procedure could be also applied to obtain the period length of the coronal rotation (PLCR) of daily MCI at each time point during the considered time interval, and the extracted results are shown in Figure 9.…”
Section: Temporal Variation Of Coronal Rotationmentioning
confidence: 99%
“…Up to now, observations and studies on solar differential rotation have taken a great achievement (Howard 1984;Schroter 1985;Snodgrass 1992; Paterno 2010; Vats & Chandra 2011;Vats 2012). However, there are still many aspects, for example, the solar-cycle related and long-term variations of solar rotation rate, unknown at the present (Komm, Howard & Harvey 1993;Ulrich & Bertello 1996;Stix 2002;Li et al 2011aLi et al , 2011b. In this study, we will investigate solar-cycle related variation of solar rotation rate, using data of the rotation rates of magnetic fields, distributed along latitudes and varying with time at the time interval of August 1976 to April 2008, and a new explanation is proposed on such a solar-cycle related variation of the solar rotation rate.…”
Section: Introductionmentioning
confidence: 99%